The mediating role of decent work perception in role clarity and job embeddedness among Chinese nurses: a cross-sectional study - Chen Fang; Yu Ran; Zheng Huan; Zhao Xiaoyan (BMC Nursing)
Abstract Background The high turnover rate of the nursing team is not only detrimental to maintaining the stability of the team, but also to providing high-quality nursing services, which is an immeasurable loss for both patients and hospitals. As a predictor variable of turnover rate, increasing the level of job embeddedness among nurses can reduce their willingness to resign. Although there are currently studies reporting the correlation between role clarity, decent work perception and job embeddedness, the mechanisms between the three have not been explored, which cannot provide scientific and effective theoretical support for developing targeted measures for job embeddedness. Methods Using convenience sampling method, 309 nurses from hospitals in 9 cities of Zhejiang Province (Hangzhou, Ningbo, Wenzhou, Huzhou, Jiaxing, Shaoxing, Lishui, Jinhua, Taizhou) China were recruited as the research subjects from July to August 2024. The General Information Questionnaire, Decent Work Perception Scale, Role Clarity Scale and Job Embeddedness Scale were used for the investigation. Results This study shows that decent work perception, role clarity, job embeddedness are all at a moderate level. The total score of job embeddedness is positively correlated with the total scores of decent work perception and role clarity, and t decent work perception plays a partial mediating effect between role clarity and job embeddedness, accounting for 88.1% of the total effect. Conclusions and implications for nursing and health policy According to the results of this study, to improve the job embeddedness level of clinical nurses, the hospital nursing department and head nurses in the department should explore different measures to stimulate the level of decent work perception of clinical nurses and improve their role clarity cognition, to enhance their job embeddedness level.